Effect of regulating anger and sadness on decision-making. Issue 6 (1st November 2016) - Szasz, Paul Lucian; Hofmann, Stefan G.; Heilman, Renata M.; Curtiss, Joshua
Abstract: The aim of the current study was to investigate the effects of reappraisal, acceptance, and rumination for regulating anger and sadness on decision-making. Participants ( N = 165) were asked to recall two autobiographical events in which they felt intense anger and sadness, respectively. Participants were then instructed to reappraise, accept, ruminate, or not use any strategies to regulate their feelings of anger and sadness. Following this manipulation, risk aversion, and decision-making strategies were measured using a computer-based measure of risk-taking and a simulated real-life decision-making task. Participants who were instructed to reappraise their emotions showed the least anger and sadness, the most adaptive decision-making strategies, but the least risk aversion as compared to the participants in the other conditions. These findings suggest that emotion regulation strategies of negative affective states have an immediate effect on decision-making and risk-taking behaviors.